The pursuit of satisfaction: Variation in satisfaction with bus transit service among riders with encumbrances and riders with disabilities using a large-scale survey from London, UK. (April 2016) - Verbich, David; El-Geneidy, Ahmed
Abstract: To retain and grow ridership, transit agencies continuously survey riders to learn how to improve services and understand what leads to rider satisfaction. Nevertheless, transit riders are not a homogeneous entity and understanding the distinctions between transit riders can help transit agencies in their efforts to provide satisfactory service to retain existing riders and attract new ones. To uncover how diverse aspects of bus services can differentially impact satisfaction of different riders, we use data from a large-scale, multiyear bus satisfaction survey from London, UK. Specifically, we model satisfaction using logistic regressions to learn how encumbered riders and riders with physical disabilities value different features of bus services compared to other types of riders. For riders traveling with large items, shopping bags, or children, we find that satisfaction depends on the presence and condition of a bus shelter and the availability of a seat. Satisfaction of riders with disabilities depends on information availability at the bus stop, as well as trip speed and reliability. Our findings indicate that improving waiting area conditions and providing information at the stop can increase the satisfaction of riders with encumbrances and disabilities, respectively. Findings from this paper can be of benefit to transit planners and policy makers as it offers new insights about the determinants of satisfaction of two groups of bus riders not often considered in the public transport literature. Highlights: Transit agencies need to understand how different users value their services. We modeled bus service satisfaction of riders with disabilities or encumbrances. Satisfaction of disabled riders depends on information at bus stops and reliability. Satisfaction of riders with encumbrances depends on a well-maintained shelter. Agencies should target waiting area features to attract these types of riders.